Coclosed Rickart Modules - Ahmed, Ghaleb; Ahmed, Ghaleb (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2018)
Let be a right module over an arbitrary ring with identity and . In this work, the coclosed rickart modules as a generalization of rickart modules is given. We say a module over coclosed rickart if for each , is a coclosed submodule of . Basic results over this paper are introduced and connections between these modules and otherwise notions are investigated.